Cholesteric-type cellulosic structures: from plants to applications - Almeida, Ana (2019)
The structural support of plant cells is provided by the cell wall, which major load-bearing component is an array of hierarchical orientedhierarchical-oriented cellulose nano-, micro- and meso-structures of cellulose microfibrils. Cellulosic structures can respond to humidity changes by expanding or shrinking and this allows, for example, the dispersion of seeds. Previous studies have shown that nanorods, extracted from cell walls, can generate lyotropic liquid crystals that are at the origin of solid cholesteric-like arrangements. Not only photonic films, but also right and left helical filaments, anisotropic films with the ability to bend back and forth under the action of a moisture gradient at room temperature, are some of the materials that were produced from cellulose liquid crystal systems. This work is a review that focus on liquid crystalline-based structures obtained from cellulosic materials and how small perturbations on their structures affect significantly the response to external stimulus and interactions with the environment. Special emphasis is given to cholesteric-like organization of cellulose structures existing in plants, which are an inspiration for the production of the next generation of soft interactive materials.